2012
DOI: 10.1530/rep-11-0259
|View full text |Cite
|
Sign up to set email alerts
|

Mouse forkhead L2 maintains repression of FSH-dependent genes in the granulosa cell

Abstract: The forkhead transcription factor forkhead box L2 (FOXL2) is expressed in granulosa cells of small and medium follicles in the mouse ovary. Foxl2 female knockout mice exhibit primordial follicle depletion and primary ovarian failure, but evidence from adult female conditional Foxl2 knockout mice suggests that FOXL2 may also play a significant role in maintenance of ovarian differentiation at stages beyond the primordial follicle and initial wave of folliculogenesis. We previously showed that human FOXL2 functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
(63 reference statements)
3
18
0
Order By: Relevance
“…The high conservation of Foxl2 sequences and mammalian expression suggests a key role in ovarian development and function [30,31]. Either human or mouse Foxl2 can function as a transcriptional repressor of StAR and CYP19A1, likely by binding to specific sites in the gene promoters [25,26,32], consistent with our results from the ChIP assay. Foxl2 is responsible for POF, and is involved in inflammation, apoptosis, reactive oxygen species metabolism, and granulosa cell tumors [3,5,33].…”
Section: Discussionsupporting
confidence: 84%
“…The high conservation of Foxl2 sequences and mammalian expression suggests a key role in ovarian development and function [30,31]. Either human or mouse Foxl2 can function as a transcriptional repressor of StAR and CYP19A1, likely by binding to specific sites in the gene promoters [25,26,32], consistent with our results from the ChIP assay. Foxl2 is responsible for POF, and is involved in inflammation, apoptosis, reactive oxygen species metabolism, and granulosa cell tumors [3,5,33].…”
Section: Discussionsupporting
confidence: 84%
“…5A and inset). As StAR is an established target of FOXL2, with FOXL2 shown to inhibit StAR transcription and gene expression in other cell types [6,58], we measured StAR mRNA expression and confirmed that the reduction in FOXL2 lead to increased StAR expression in GCs (Fig. 5A).…”
Section: Resultsmentioning
confidence: 53%
“…FOXL2 is important for ovarian development and function 104, 105 , and it promotes female sex determination 100, 106, 107 . Mutations in the human FOXL2 gene result in an autosomal dominant, loss of function disease called blepharophimosis, ptosis, and epicanthus inversus syndrome (BEPS), which causes eyelid abnormalities and premature ovarian failure 108 .…”
Section: Emerging Roles For Additional Transcription Factor Families:mentioning
confidence: 99%